Gender bias in health research: implications for women's health in Kerala (India) and Sri Lanka - Thresia, C. U. and Mohindra, K. S (Critical Public Health, 2011)
Indian state of Kerala, and Sri Lanka have a special place in global health discourses, although there has been a relatively little systematic analysis of women’s health in these societies. Moreover, there are a number of dimensions of women’s health that have been underappreciated by public health researchers and development experts due to systematic gender biases in health research. This article seeks to provide a more complete picture of women’s health in Kerala and Sri Lanka by explicitly addressing three key gender biases: inattention to health issues that particularly affect women, incomplete approaches to understanding the health of women and insufficient attention paid to the interactions between gender and other social stratification, such as class, ethnicity or caste.